Focused ultrasound-mediated small-molecule delivery to potentiate immune checkpoint blockade in solid tumors - Wu, Qiuyu; Xia, Yuanhang; Xiong, Xiaohe; Duan, Xinxing; Pang, Xiaoxiao; Zhang, Fugui; Tang, Song; Su, Junlei; Wen, Shuqiong; Mei, Li; Cannon, Richard D.; Ji, Ping; et al. (Frontiers in Pharmacology, 2023)
In the last decade, immune checkpoint blockade (ICB) has revolutionized the standard of treatment for solid tumors. Despite success in several immunogenic tumor types evidenced by improved survival, ICB remains largely unresponsive, especially in “cold tumors” with poor lymphocyte infiltration. In addition, side effects such as immune-related adverse events (irAEs) are also obstacles for the clinical translation of ICB. Recent studies have shown that focused ultrasound (FUS), a non-invasive technology proven to be effective and safe for tumor treatment in clinical setting, could boost the therapeutic effect of ICB while alleviating the potential side effects. Most importantly, the application of FUS to ultrasound-sensitive small particles, such as microbubbles (MBs) or nanoparticles (NPs), allows for precise delivery and release of genetic materials, catalysts and chemotherapeutic agents to tumor sites, thus enhancing the anti-tumor effects of ICB while minimizing toxicity. In this review, we provide an updated overview of the progress made in recent years concerning ICB therapy assisted by FUS-controlled small-molecule delivery systems. We highlight the value of different FUS-augmented small-molecules delivery systems to ICB and describe the synergetic effects and underlying mechanisms of these combination strategies. Furthermore, we discuss the limitations of the current strategies and the possible ways that FUS-mediated small-molecule delivery systems could boost novel personalized ICB treatments for solid tumors.